2021
DOI: 10.7759/cureus.18844
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Autonomic Modulation and Anti-Thyroid Peroxidase (TPO) Antibodies in Subclinical Hypothyroidism – Does Any Correlation Exist?

Abstract: Background: Heart rate variability (HRV) reflects the balance between the sympathetic and parasympathetic divisions of the autonomic nervous system. Anti-thyroid antibodies like anti-TPO and anti-Thyroglobulin have long been associated with thyroid dysfunction and abnormal thyroid profile testing. Subclinical hypothyroidism (SCHypo) is characterized by elevated thyroid-stimulating hormone (TSH) with normal thyroid hormones. We hypothesize that autonomic function may be deranged in anti-TPO positive subclinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
3
3
0
Order By: Relevance
“…27 Both our study and other examples show that subclinical hypothyroidism and especially Anti-TPO positivity in this group have significant effects on the fetal heart. 26,27 Anti-TPO and Anti-TG antibodies that can cross the placenta are present in 3%−18% of pregnancies, and this rate was 16.9% in our study, which is consistent with the literature. 28 In cardiomyocytes, thyroid hormones regulate the β-adrenergic system and reninangiotensin-aldosterone system (RAS).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…27 Both our study and other examples show that subclinical hypothyroidism and especially Anti-TPO positivity in this group have significant effects on the fetal heart. 26,27 Anti-TPO and Anti-TG antibodies that can cross the placenta are present in 3%−18% of pregnancies, and this rate was 16.9% in our study, which is consistent with the literature. 28 In cardiomyocytes, thyroid hormones regulate the β-adrenergic system and reninangiotensin-aldosterone system (RAS).…”
Section: Discussionsupporting
confidence: 92%
“…reported that the babies of women with subclinical hypothyroidism had higher systolic and diastolic blood pressures than the control group 27 . Both our study and other examples show that subclinical hypothyroidism and especially Anti‐TPO positivity in this group have significant effects on the fetal heart 26,27 …”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In contrast, we observed a more pronounced association for functional parameters of the autonomic nervous system. Several studies and animal experiments found altered cardiovascular autonomic function in subclinical or overt hypothyroidism [53][54][55][56][66][67][68][69][70] . However, the evidence for a potential role of autoimmunity in euthyroid subjects is much weaker.…”
Section: Discussionmentioning
confidence: 99%